ISOLATION AND CHARACTERIZATION OF XANTHOMONAS AXONOPODIS FROM CITRUS AURANTIFOLIA CHRISTM (SWINGLE.) - B.SUJATHA; D.V.R. SAI GOPAL (The Bioscan, 2010)
Citrus Canker was caused by Xanthomonas axonopodis. It causes serious damage to Citrus industry. The pathogen was isolated from the infected fruits of citrus orchards in the present study. It was characterized by preliminary studies and identified as gram negative rod shaped organism. Analysis of the protein profiles by SDS-PAGE revealed differences. A change was observed in total proteins, soluble and insoluble proteins. Total proteins showed difference between 116 KDa and 18.4 KDa with reference to the marker. Plasmid DNA analysis also showed differences. These differences in the protein and plasmid profile quote the pathogenicity of the bacteria towards the citrus crop.